After the wedding [videorecording (DVD)] - Freundlich, Bart, 1970-; Williams, Michelle, 1980-; Moore, Julianne; Crudup, Billy, 1968-; Chase, Will, 1970- (Sony Pictures Home Entertainment, 2019)
Isabel has devoted her life to working with the children in a Calcutta orphanage. Theresa is the multimillionaire leader of a media company who lives with her artist husband in New York. When Isabel hears of a mysterious and generous grant for the financially strained orphanage, she must travel to New York to meet the benefactor, Theresa, in person, who then insists she stay for a family wedding.